Complete plastid genome of Lespedeza tricolor (Fabaceae), an endemic shrub in Korea. Issue 10 (3rd October 2022) - Kim, Tae-Hee; Kim, Sang-Chul; Ha, Young-Ho; Choi, Kyung; Kim, Hyuk-Jin
Abstract: Lespedeza tricolor is a species found in the southern province of Korea, thought to be endemic to Korea. The complete plastid genome of this legume was sequenced in this study. DNA from L. tricolor was extracted, sequenced, and assembled into the complete plastid genome. We used 18 species of the family Fabaceae and 77 protein-coding genes to perform phylogenetic analysis. The plastid genome is 149, 038 bp in length, with large (82, 495 bp) and small (18, 889 bp) single-copy regions, separated by a pair of inverted repeat regions (23, 827 bp). It contains 83 protein-coding genes, eight rRNAs, 37 tRNAs, and two pseudogenes ( rpl22 and infA ). Our phylogenetic analysis suggests that the genus Lespedeza is monophyletic and L. tricolor is closely related to L. maritima and L. buergeri . In this study, we identified the phylogenetic position of L. tricolor and provided the data that can be used in various ways in future studies.